Rising Caesarean Section Rate – Whether Women Choice, Doctor Preference or Clinical /Non Clinical Indications are Responsible. - Noreen Majeed ,ShabanaKalsoom,Humera Rani; Shamsa Tariq (Journal of Rawalpindi Medical College, 2018)
Background : To determine the factors responsible for the rise in caesarean section rates whether women choice, doctor preference or clinical /non clinical indications are responsible. Methods: In this observational study antenatal patients of any age ,with any previous obstetric history and parity were asked about their wishes regarding mode of deliveries in the current pregnancy irrespective of any clinical consideration. Actual indications for caesarean done in the next 3 months were noted down and rate of caesarean and frequencies for each caesarean indication were calculated. Discussions with doctors regarding reasons for caesarean decisions in their practices were done and percentages were calculated for major indications of caesarean in their practice. Results:Among 558 antenatal women, majority (74.1%) wished for vaginal delivery. Total caesarean rate in 3 months was 42.8%. Previous one caesareans(24.67%) or previous multiple caesareans(21.83) were the commonest indications. Clinicians revealed suspected fetal compromise(intrapartum)(76.6%), previous one caesareans(66.6%) and previous multiple caesareans(50%) as the common indications. No doctor agreed on economic incentive being the sole reason for caesarean in their practice. Conclusion: Majority of women wish to deliver vaginally. The main reason for rise in caesarean rate are clinical indications like previous one and multiple caesareans , suspected fetal compromise(intrapartum) and failure to progress. Risk minimizing behaviour is prominent among non clinical reasons for caesarean delivery.